Royal Education Award (Pingat Jaya Cemerlang) from UMPSA, a sweet gift for Foo Xiao Bing - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (UMPSA, 2023)
GAMBANG, 21 October 2023 - All her hard work and effort at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) finally paid off whenFoo Xiao Bing, 24, was awarded the Royal Education Award (Pingat Jaya Cemerlang) at the UMPSA 18th Convocation Ceremony (MKK-18).